Pengaruh Pengalaman Kerja, Kompetensi dan Kecerdasan Emosional Terhadap Prestasi Kerja Pegawai Studi Kasus Kantor Dinas Pendidikan Kota Solok - Miza Maiyanti; Afni Yeni; Arfimasri Arfimasri (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This research was conducted at the Solok City Education Office, the purpose of this research was to determine the effect of work experience, competence and emotional intelligence on employee performance at the Solok City Education Office. In this study, the population was employees at the Solok City Education Office, totaling 82 people. By using purposive sampling, a sample of 41 people was obtained. The data collection technique used is by using a questionnaire or questionnaire. Based on multiple linear regression analysis of the variables Work Experience, Competence and Emotional Intelligence affect Employee Performance. Y = 11.627 a + 0.029 X1 + 0.354 X2 + 0.339 X3. From the t test conducted, it was found that the variable X1 Work Experience had a significant effect on Employee Performance with a variable value of 0.265 > 1.687 and a significant value level of 0.042 < 0.05. Variable X2 Competence has a significant effect on employee performance with a variable value of 1.896 > 1.687 and a significant value level of 0.026 < 0.05. variable X3 Emotional Intelligence has a significant effect on Employee Performance with a variable value of 2.109> 1.687 and a significant value level of 0.031 < 0.05. From the f test conducted, it was found that Work Experience, Competence and Emotional Intelligence have a simultaneous effect on Employee Work Performance F count is 22.391 > F table 2.859 and with this the significance is 0.000 < 0.05.